Pengaruh Penerapan Strategi : PAKEM Project Based Learning Pada Mata Pelajaran Fiqh Terhadap Hasil Belajar Siswa Pada Kelas VII Di SMPIT Al-Falaah Simo Tahun Ajaran 2022/2023 - Al Adaby, Hanifha; Abdullah Khair, Mulyanto; Faridatul Ulfah, Yetty (STIT Sirojul Falah Bogor, 2023)
This study aims to determine: (1) the learning outcomes of seventh grade students when using the PAKEM strategy: project based learning. (2) to determine the effect of the application of the PAKEM strategy: project based learning in fiqh class VII subjects at SMPIT Al-Falaah Simo in the 2022/2023 school year. This type of research is descriptive quantitative, using the statistical-correlative analysis method in order to know the strength of the relationship between two variables can be positively or negatively correlated. The population in this study were seventh grade students consisting of classes A and B at SMPIT Al-Falaah Simo. Sampling using probability sampling technique with simple random sampling method. Data collection in this study included documentation and questionnaires. While the data analysis technique in this study uses the Person product Moment formula. In the prerequisite test using the Kolmogorov Smirnov normality test, linearity test, correlation coefficient significance test using the Product Moment formula, and hypothesis testing using the SPSS version 25 application. The results of this study resulted in a significance value of 0.003 (Sig <0.05) which means that there is a relationship between the variable application of the project-based learning model and the learning outcomes variable. In addition, it was found that the correlation coefficient value was 0.000, this shows that there is a fairly strong relationship between the variables of the effect of the application of the project-based learning model and learning outcomes.